2012
DOI: 10.1152/ajplung.00321.2011
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 regulates migration of lung alveolar epithelial cells through activation of Rac1 and matrix metalloproteinase-2

Abstract: Ghosh MC, Makena PS, Gorantla V, Sinclair SE, Waters CM. CXCR4 regulates migration of lung alveolar epithelial cells through activation of Rac1 and matrix metalloproteinase-2. Am J Physiol Lung Cell Mol Physiol 302: L846 -L856, 2012. First published February 17, 2012 doi:10.1152/ajplung.00321.2011.-Restoration of the epithelial barrier following acute lung injury is critical for recovery of lung homeostasis. After injury, alveolar type II epithelial (ATII) cells spread and migrate to cover the denuded surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 60 publications
4
48
0
2
Order By: Relevance
“…The significant association between lung CXCL12 concentrations and fibrocyte numbers in our model supports previous studies that demonstrated the importance of CXCL12 in fibrocyte recruitment (12,13). CXCL12 secretion is induced in rat Type II epithelial cells after scratch injury, implicating the epithelium as an important source of CXCL12 (38). In patients with IPF, epithelial cells expressed CXCL12 at higher concentrations than in control samples (14).…”
Section: Discussionsupporting
confidence: 88%
“…The significant association between lung CXCL12 concentrations and fibrocyte numbers in our model supports previous studies that demonstrated the importance of CXCL12 in fibrocyte recruitment (12,13). CXCL12 secretion is induced in rat Type II epithelial cells after scratch injury, implicating the epithelium as an important source of CXCL12 (38). In patients with IPF, epithelial cells expressed CXCL12 at higher concentrations than in control samples (14).…”
Section: Discussionsupporting
confidence: 88%
“…The kinetics of the relative wound density (RWD) was analyzed by IncuCyte TM software. Wound Healing Assay-Cell migration was measured according to the previously described method (16). In brief, the confluent monolayers of fibroblast cells were wounded by scraping with a pipette tip across the monolayer.…”
Section: Animals-mrp4mentioning
confidence: 99%
“…Chemokines are also important regulators of Rac1, one of them, CXCL12 (also known as SDF-1a) activates Rac1, decreases cAMP levels, and favors prostate cancer cells migration (21)(22)(23). In addition, CXCR4, the CXCL12 receptor, is frequently overexpressed in malignant epithelial cells, and the CXCL12/CXCR4 axis plays a pivotal role in directing the metastasis of CXCR4-positive tumor cells to organs that express CXCL12, such as lungs, liver, and bones (24,25).…”
Section: Introductionmentioning
confidence: 99%